Gata5 is required for the development of the heart and endoderm in zebrafish - Reiter, Jeremy F. (Cold Spring Harbor Laboratory Press, 1999)
The mechanisms regulating vertebrate heart and endoderm development have recently become the focus of intense study. Here we present evidence from both loss- and gain-of-function experiments that the zinc finger transcription factor Gata5 is an essential regulator of multiple aspects of heart and endoderm development. We demonstrate that zebrafish Gata5 is encoded by the faust locus. Analysis of faust mutants indicates that early in embryogenesis Gata5 is required for the production of normal numbers of developing myocardial precursors and the expression of normal levels of several myocardial genes including nkx2.5. Later, Gata5 is necessary for the elaboration of ventricular tissue. We further demonstrate that Gata5 is required for the migration of the cardiac primordia to the embryonic midline and for endodermal morphogenesis. Significantly, overexpression of gata5 induces the ectopic expression of several myocardial genes including nkx2.5 and can produce ectopic foci of beating myocardial tissue. Together, these results implicate zebrafish Gata5 in controlling the growth, morphogenesis, and differentiation of the heart and endoderm and indicate that Gata5 regulates the expression of the early myocardial gene nkx2.5.